Czech version of the Trail Making Test: normative data and clinical utility - Bezdicek, Ondrej; Motak, Ladislav; Axelrod, Bradley N; Preiss, Marek; Nikolai, Tomas; Vyhnalek, Martin; Poreh, Amir; Ruzicka, Evzen (Archives of clinical neuropsychology, 2012)
The Trail Making Test (TMT) comprises two psychomotor tasks that measure a wide range of visual-perceptual and executive functions. The purpose of this study was to provide Czech normative data and to examine the relationship between derived TMT indices and demographic variables. The TMT was administered to 421 healthy adults. Two clinical groups (n = 126) were evaluated to investigate the clinical utility of the TMT-derived scores: amnestic mild cognitive impairment (n = 90) and Alzheimer's disease (n = 36). Statistical analyses showed that age and education, but not gender, were significantly associated with TMT completion times and derived scores. Of all the indices, only the TMT ratio score was insensitive to age. We present normative values for the Czech version of the TMT, providing a reference for measuring individual performance in native Czech speakers. Moreover, we found that accuracy on the TMT was improved with the attenuation of age.
Keywords: Alzheimerova nemoc; Cognitive Dysfunction; Adult; senioři; Aging; Aged; Male; lidé; kognitivní dysfunkce; lidé středního věku; Humans; stárnutí; Age Factors; exekutivní funkce; Middle Aged; věkové faktory; referenční hodnoty; Reference Values; Psychomotor Performance; Czech Republic; senioři nad 80 let; Aged, 80 and over; mužské pohlaví; test cesty; dospělí; zraková percepce; Česká republika; ženské pohlaví; Alzheimer Disease; psychomotorický výkon; Female; Trail Making Test; Visual Perception; Executive Function